Culturally sensitive prevention programs for substance use among adolescents of color: A systematic review and meta-analysis of randomized controlled trials. (February 2023) - Bo, Ai; Goings, Trenette Clark; Evans, Caroline B.R.; Sharma, Anjalee; Jennings, Zoe; Durand, Brenna; Bardeen, Angela; Murray-Lichtman, Andrea
Abstract: This systematic review and meta-analysis aims to synthesize the efficacy of culturally sensitive prevention programs for substance use outcomes among U.S. adolescents of color (aged 11 to 18 years old) and explore whether the intervention effects vary by participant and intervention characteristics. Eight electronic databases and grey literature were searched for eligible randomized controlled trials through September 2022. Robust variance estimation in meta-regression was used to synthesize treatment effect size estimates and to conduct moderator analysis. After screening, 30 unique studies were included. The average treatment effect size across all substance use outcomes (including 221 effect sizes) was Hedges's g  = −0.20, 95% CI = [−0.24, −0.16]. The synthesized effect sizes were statistically significant across types of substances (alcohol, cigarette, marijuana, illicit and other drugs, and unspecified substance use), racial/ethnic groups (Hispanic, Black, and Native American), and different follow-ups (0–12 months, >12 months). Very few studies reported substance use consequences as outcomes and the synthesized effect size was non-significant. Meta-regression findings suggest that the intervention effects may vary based on the type of substance. This meta-analysis found supportive evidence of culturally sensitive prevention programs' efficacy in preventing or reducing substance use among Black, Hispanic, and Native American adolescents. More substance use prevention efforts and evidence is needed for Asian American, Pacific Islander, and multiracial adolescents. Highlights: Culturally sensitive programs can prevent substance use among Black, Hispanic, and Native American youth Program effects may differ based on the type of substance More studies are needed for Asian American, Pacific Islander, and multiracial youth